Application chitosan derivatives as inhibitor corrosion on steel with fluidization method - Suyanto, Dr. Ir. M.Si. (2015)
Chitosan derivatives are carboxy methyl chitosan-benzaldehyde (CMChi-B) and carboxy methyl chitosan-urea-glutaric acid (CMChi-UGLU) were synthesized from chitosan. CMChi-B and CMChi-UGLU have been used as new corrosion inhibitor on steel with fluidization method. In this research, corrosion media was NaCl 2% solution and value of maximum inhibition efficiency for CMChi-B and CMChi-UGLU respectively were 80,82% and 80.62%.